Algebra and other relevant physics skills: The effectiveness of mastery practice on skills accuracy and exam grade in introductory physics - Qiaoyi Liu; Harish Moni Prakash; Andrew F. Heckler (Physical Review Physics Education Research)
We conducted two studies to investigate the extent to which brief, spaced, mastery practice on skills relevant to introductory physics affects student performance. The first study investigated the effect of practice of “specific” physics skills, each one relevant to only one or a few items on the course exam. This study employed a quasiexperimental design with 766 students assigned to “intervention” or “control” conditions by lecture section sharing common exams. Results of the first study indicate significant improvement in the performance for only some of the exam items relevant to the specific skills practiced. We also observed between-section performance differences on other exam items not relevant to training, which may be due to specific prior quiz items from individual instructors. The second study investigated the effect of practice on the “general” skill of algebra relevant to introductory physics, a skill which was relevant to most of the exam items. This study employed a similar quasiexperimental design with 363 students assigned to treatment or control conditions, and we also administered a reliable pre- and post-test assessment of the algebra skills that was iteratively developed for this project. Results from the second study indicate that 75% of students had high accuracy on the algebra pretest. Students in the control condition who scored low on the pretest gained about 0.7 standard deviations on the post-test, presumably from engagement with the course alone, and students in the algebra practice condition had statistically similar gains, indicating no observed effect of algebra practice on algebra pre- to post-test gains. In contrast, we find some potential evidence that the algebra practice improved final exam performance for students with high pretest scores and did not benefit students with low pretest scores, although this result is inconclusive: the point estimate of the effect size was 0.24 for high pretest scoring students, but the 95% confidence interval [−0.01, 0.48] slightly overlapped with zero. Further, we find a statistically significant positive effect of algebra practice on exam items that have higher algebraic complexity and no effect for items with low complexity. One possible explanation for the added benefit of algebra practice for high-scoring students is fluency in algebra skills may have improved. Overall, our observations provide some evidence that spaced, mastery practice is beneficial for exam performance for specific and general skills, and that students who are better prepared in algebra may be especially benefitting from mastery practice in relevant algebra skills in terms of improved final exam performance.